ANALYSIS OF THE ACTIVITIES OF SMALL BUSINESS AND ENTREPRENEURIAL ENTITIES IN THE REPUBLIC OF UZBEKISTAN (World Bulletin of Social Sciences, 2023)
The main important feature of SME activities in the Republic of Uzbekistan is that it shapes the competitive environment and directly contributes to the high level of economic development achieved today
Keywords: level; achieved; Republic